2021
DOI: 10.1002/acm2.13233
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prostate intensity‐ and volumetric‐modulated arc radiation therapy planning quality with PlanIQTM

Abstract: Purpose The purpose of this study was to assess the quality of treatment planning using the PlanIQTM software and to investigate whether it is possible to improve the quality of treatment planning using the “Feasibility dose‐volume histogram (DVH)TM” implemented in the PlanIQTM software. Methods Using the PlanIQTM software, we retrospectively analyzed the learning curve regarding the quality of the treatment plans for 148 patients of prostate intensity‐modulated radiation therapy and volumetric‐modulated radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These results were achievable due to the accumulated expertise acquired over the years of working with prostate cancer patients and using the same planning system. Sasaki et al [ 40 ] retrospectively analyzed 148 plans over eight years using the PlanIQ™ software for learning curve evaluation and showed a trend of improvement in the quality of the plans over each successive year. Moreover, in all cases where re-planning was performed, the new treatment plan was better than the initial clinical plan administered to patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results were achievable due to the accumulated expertise acquired over the years of working with prostate cancer patients and using the same planning system. Sasaki et al [ 40 ] retrospectively analyzed 148 plans over eight years using the PlanIQ™ software for learning curve evaluation and showed a trend of improvement in the quality of the plans over each successive year. Moreover, in all cases where re-planning was performed, the new treatment plan was better than the initial clinical plan administered to patients.…”
Section: Discussionmentioning
confidence: 99%
“…To predict the complexity of clinical plans in advance, PlanIQ was used to evaluate the quality of the treatment plans. To evaluate the quality of clinical plans using PlanIQ, we adopted the “plan quality metric” (PQM) algorithm implemented in PlanIQ [ 8 ]. The PQMs used in this study were based on 28 treatment plans for 16 patients who underwent head-and-neck VMAT at our institution, as described above.…”
Section: Methodsmentioning
confidence: 99%
“…It scores the quality of treatment plans, objectively evaluates them, and calculates the ideal dose-volume histogram (DVH), which is expected to be used in clinical applications. Previous studies have evaluated the quality of treatment plans using PlanIQ [6][7][8] and improved the treatment plans before and after the intervention of PlanIQ [9][10][11]. However, no study has examined the efficiency of dose verification and dose validation using ideal treatment plans.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that confirming the FDVH for OARs calculated using PlanIQ before treatment planning can help reduce the variation in quality from one treatment plan to another [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%